The possession of Alba Díaz - Cañas, Isabel (Berkley, 2025)
"When a demonic presence awakens deep in a Mexican silver mine, the young woman it seizes must turn to the one man she shouldn't trust... from bestselling author Isabel Cañas. In 1765, plague sweeps through Zacatecas. Alba flees with her wealthy merchant parents and fiancé, Carlos, to his family's isolated mine for refuge. But safety proves fleeting as other dangers soon bare their teeth: Alba begins suffering from strange hallucinations, sleepwalking, and violent convulsions. She senses something cold lurking beneath her skin. Something angry. Something wrong. Elías, haunted by a troubled past, came to the New World to make his fortune and escape his family's legacy of greed. Alba, as his cousin's betrothed, is none of his business. Which is of course why he can't help but notice her every time she enters a room or the growing tension between them... and why he notices her deteriorate when the demon's thirst for blood grows stronger. In the fight for her life, Alba and Elías become entangled with the occult, the Church, long-kept secrets, and one another... not knowing that one of these things will spell their doom"--